STUDY OF R AND S WAVE VOLTAGES OF ELECTROCARDIOGRAM (ECG) IN SMOKERS AND ALCOHOLICS - VENKATESH G; KRISHNAMURTHY U (International Journal of Pharma and Bio Sciences, 2014)
The Electrocardiogram (ECG or EKG) is a simple and noninvasive, inexpensive test helps in assessing the cardiovascular status. Chronic smoking and chronic consumption of alcohol induce changes in various components of the ECG and are established. R voltage and S voltage represent the early and late depolarization of the ventricles and these are less addressed in the literature with respect to smoking and alcoholism. Hence we intended to study the same. Age, height and weight matched smokers, alcoholics and non alcoholic non smoking group were selected from the population constituting 50 adult men in each group. The ECG was recorded; R voltage, S voltage and Ventricular activation time (VAT) were analyzed. Heart rate was significantly increased in both alcoholics and smokers. R and S voltages were decreased both in smokers and alcoholics. VAT was increased. This study showed that smokers and alcoholics are at risk for conduction problems also.